Paroxysmal Supraventricular Tachycardia with Wolff-Parkinson-White Syndrome in a Neonate - T.S. Kustiman; J. Abdulkadir; A. Alisjahbana (Indonesian Pediatric Society, 1979)
A case of paroxysmal supraventricular tachycardia with Wolff-Parkinson-White syndrome in an Indonesian neonate born in the Departement of Obstetrics, Dr. Hasan Sadikin General Hospital, Bandung, is reported. Tachycardia in the neonate was first noted at the age of 6 days, but the heart rate gradually decreased in 8 hours after oxygen was administered. Electrocardiographic examination revealed a Wolff-Parkinson-White syndrome. A second attack of tachycardia occurred at the age of 2 months and the infant was immediately hospitalized and treated with lanoxin. Serial electrocardiographic examination still revealed the same syndrome. The management and prognosis of supraventricular tachycardia in the neonate is also discussed.